RNA-binding protein DAZAP1 accelerates the advancement of pancreatic cancer by inhibiting ferroptosis - Xinqing Wang; Hao Fan; Xiaoping Ye; Yu Hu; Yan Xiao; Ming Zhang; Yonghui Xu; Jianjun Song; Yongyun Luo (European Journal of Medical Research)
Abstract Background Pancreatic cancer (PC) is a highly aggressive malignancy with a poor prognosis due to its late-stage diagnosis and limited treatment options. Objectives This study aimed to elucidate the molecular mechanisms underlying PC progression and identify potential molecular targets for its diagnosis and treatment. Methods DAZAP1 expression in PC tissues, normal tissues and cell lines was assessed using immunohistochemistry (IHC), reverse transcription–quantitative polymerase chain reaction (RT–qPCR) and western blotting. DAZAP1 knockdown was achieved through plasmid transfection, and its effects on ferroptosis and PC progression were evaluated using RT–qPCR, western blotting, CCK-8 assays, EdU staining, Fe2+ content measurement, reactive oxygen species (ROS) detection, wound healing and Transwell migration assays. Results DAZAP1 expression was significantly upregulated in PC tissues and cell lines compared to normal counterparts. DAZAP1 knockdown suppressed PC cell proliferation and induced ferroptosis, while ferroptosis inhibition reversed these effects, enhancing PC cell proliferation and metastasis. Conclusions DAZAP1 suppression promotes ferroptosis, thereby inhibiting PC cell proliferation and metastasis. These findings suggest that DAZAP1 is a potential therapeutic target for PC.